The perspectives of the North-South Dialogue: Elements for a reorientation - Hans Mayrzedt; Mario Ernst (Intereconomics, 1981)
During the 1970s the North-South Dialogue, which will shortly be continued at the summit in Mexico, was characterized by a gross disproportion between monstrous expenditure—with many losses due to friction —and negligible results. Symptoms of fatigue with regard to the Dialogue are spreading not only among governments, but also among the public in the North. The disillusionment and disappointment are proportionally greater in the South. As no one would presumably like to risk a failure of the Dialogue, which would probably result in a severe aggravation of the North-South conflict, a reorientation of the Dialogue now suggests itself.
Keywords: 330; North-South Dialogue